Untitled (African Knowledges and the History Publication since the 1970s)
Tapings of various objects of African cultural heritage displayed in the National Museum (of Liberia) without verbal narration.
Keywords: Education; Singing; Dance; Cultural Heritage; African Cultural Heritage